Gaining an advantage by sitting an OSCE after your peers: A retrospective study. (2nd November 2018) - Ghouri, Asim; Boachie, Charles; McDowall, Suzanne; Parle, Jim; Ditchfield, Carol A.; McConnachie, Alex; Walters, Matthew R.; Ghouri, Nazim
Abstract: Purpose: To investigate if final year medical students undertaking an OSCE station at a later stage during examination diet were advantaged over their peers who undertook the same station at an earlier stage, and whether any such effect varies by the student's relative academic standing. Methods: OSCE data from six consecutive final year cohorts totaling 1505 students was analyzed. Mixed effects logistic regression was used to model factors associated with the probability of passing each individual station (random effects for students and circuits; and fixed effects to assess the association with day of examination, time of day, gender and year). Results: Weaker students were more likely to pass if they took their OSCE later in the examination period. The odds of passing a station increased daily by 20%. Overall, the mean number of stations passed by each student increased over the 5 days. Conclusions: Students undertaking the same OSCE stations later in examination period statistically had higher chances of passing compared to their peers, and the weaker students appear to be particularly advantaged. These findings have major implications for OSCE design, to ensure students are not advantaged by examination timing, and weaker students are not "passing in error".